EFEKTIVITAS PENERAPAN PIDANA MATI TERHADAP PELAKU TINDAK PIDANA KORUPSI DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI - Febri Edvio Rinaldo`SN; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Corruption is (from latin: corruption, bribery corruptore meaning ruin) symptoms in which the officials of the State bodies, misusing authority with the occurrence of bribery, counterfeiting, as well as other irregularities. According to Klitgaard corruption is a malignant disease that is eroding the health of community such as cancer diseases which step by step suppress human life.This type of research is classed in the normative legal research. The source is a secondary data are differentiated into 3 (three), that is the primary legal materials, legal secondary materials and materials law tertier. In the collection of using the method of the study of librarianship or documentary studies. The were analyzed quantitatively, outlines are descriptive of the data obtained. In drawing inferences using a deductive method of thought, that is the way of thinking that draws a conclusion from a statement or proposition that is a public statement or case is special.Of research results, first, how the application of criminal death in Act No. 31 of 1999 jo Act No. 20 of 2001 about the eradication of criminal acts of corruption? Second,how the effectiveness of the application of the criminal dead perpetrators of criminal corruption in Indonesia based on Act No. 31 of 1999 jo Act No. 20 of 2001 about the eradication of criminal acts of?The author's suggestion, first considering the negative effects of corruption is very large and dangerous to the survival of the State, the criminal dead formulation should retained and applied to the provisions pengancamannya in the legislation must be set selectively and firmer. Second, should the law enforcement, such as prosecutors, judges, and all the associated apparatus had to be more assertive and more daring again to apply the criminal died for the crime of corruption perpetrators.Keywords: Criminal Dead – A Criminal Offence – Corruption.